Manajemen Pendidikan Berbasis Sekolah Sebagai Upaya Peningkatan Kualitas Pendidikan di SD Negeri 2 Sulanyah - Ni Luh Juniartini Eka Putri; Ni Made Intan Milantari; Veronika Km Diah kurniawati; Ni Komang Ayu Juliani; Basilius Redan Werang; Dewa Ayu Novi Kusumawardani (INDO PUBLISHING, 2026)
This study aims to analyze the role of school-based educational management in improving the quality of education at SD Negeri 2 Sulanyah. The method used is a qualitative approach with a literature study, which is sourced from scientific journals, books, articles, and relevant official documents. Data collection techniques were carried out through the identification, review, and analysis of various references with high credibility and authenticity. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that educational management plays a crucial role in managing educational resources effectively and efficiently to achieve educational goals. The implementation of school-based management at SD Negeri 2 Sulanyah contributes to improving the quality of learning through systematic planning, good organization, and the active involvement of school principals and all stakeholders. Furthermore, data-driven and participatory educational planning is a crucial factor in improving the quality of education sustainably. Thus, sound educational management is key to creating quality basic education and producing superior human resources improving the quality of education at SD Negeri 2 Sulanyah. The method used is a qualitative approach with a literature study, which is sourced from scientific journals, books, articles, and relevant official documents. Data collection techniques were carried out through the identification, review, and analysis of various references with high credibility and authenticity. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that educational management plays a crucial role in managing educational resources effectively and efficiently to achieve educational goals. The implementation of school-based management at SD Negeri 2 Sulanyah contributes to improving the quality of learning through systematic planning, good organization, and the active involvement of school principals and all stakeholders. Furthermore, data-driven and participatory educational planning is a crucial factor in improving the quality of education sustainably. Thus, sound educational management is key to creating quality basic education and producing superior human resources.